Effect of acid corrosion on physico-mechanical parameters and energy dissipation of granite - Zhang, Jimiao; Zhang, Bao; Shen, Yupeng; Yang, Tuo (Frontiers in Earth Science, 2024)
In deep underground engineering, it is inevitable that portions of the rock mass will be subjected to the erosion and chemical corrosion of infiltrating water. A comprehensive study of the physical, mechanical, and energetic properties of rocks after hydrochemical corrosion is crucial for ensuring the stability of the rock mass. The novelty of this research lies in the detailed investigation of the macroscopic and microscopic morphologies of rocks exposed to various corrosive solutions, as well as the changes in various physical and mechanical parameters. Utilizing the weighting method, a scientific comprehensive evaluation system for deep rocks after hydrochemical corrosion has been established. The results indicate a pronounced sensitivity of the macroscopic and microscopic morphologies to pH values. The longitudinal wave velocity of the corroded rock decreases obviously, with the maximum decrease being 13.46%. As the pH value decreases (from 7 to 3), the compressive strength, elastic modulus, cohesion, and internal friction angle of the rocks all decrease significantly. The acidity of the solution significantly aects the changes in the three types of strain energy of the rocks, with higher acidity leading to weaker energy storage capability. Among the factors influencing the characteristics of strain energy variation in rocks, confining pressure has a higher priority than pH value. This study precisely evaluates the impact of hydrochemical corrosion on rock damage using a percentage-based scoring system, and found that granite’s score dropped from 81 to 16. The research findings provide valuable insights for the evaluation of rock mass stability under hydrochemical corrosion conditions.